2021
DOI: 10.3389/fimmu.2020.631809
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Taxifolin Protects Against Dextran Sulfate Sodium-Induced Colitis via NF-κB Signaling, Enhancing Intestinal Barrier and Modulating Gut Microbiota

Abstract: Taxifolin is a natural antioxidant polyphenol with various bioactivities and has many beneficial effects on human gut health. However, little is known of its function on colitis. In this study, the protective effects of taxifolin on colitis symptoms, inflammation, signaling pathways, and colon microbiota were investigated using dextran sulfate sodium (DSS)-induced colitis mice. Intriguingly, pre-administration of taxifolin alleviated the colitis symptoms and histological changes of the DSS-challenged mice. Sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
29
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 44 publications
10
29
1
Order By: Relevance
“…Moreover, SCH inhibited the degradation of p-I κ B α , which is essential for NF- κ B activation, in a dose-dependent manner. Our results suggested that SCH may alleviate allergic airway inflammation by inhibiting the NF- κ B pathway, similar to a previous study [ 30 ].…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, SCH inhibited the degradation of p-I κ B α , which is essential for NF- κ B activation, in a dose-dependent manner. Our results suggested that SCH may alleviate allergic airway inflammation by inhibiting the NF- κ B pathway, similar to a previous study [ 30 ].…”
Section: Discussionsupporting
confidence: 92%
“…In past studies, the gut microbiota in colitis shows decreased ratios of Firmicutes to Bacteroidetes. 44,45 We further calculated the ratio of Firmicutes to Bacteroidetes, the ratio of Firmicutes to Bacteroidetes in our results was 4.0%, 1.0% and 1.5% in the control, DSS and Amuc_2109 groups, respectively (Fig. 6E).…”
Section: Food and Function Papermentioning
confidence: 73%
“…In our lab, we found that polyphenol taxifolin changed the composition of colonic microbial community by 16S rDNA sequencing. The change in Bacteroides, Clostridium saccharogumia, Clostridium ramosum, Sphingobacterium multivorum, and Bacteroidetes/Firmicutes ratio caused by dextran sulfate sodium was restored by taxifolin to relieve mice colitis [129]. In conclusion, plant polyphenols can promote beneficial bacteria in the process of regulating intestinal microbes.…”
Section: Regulation Of Polyphenols On Gut Microbiotamentioning
confidence: 85%